Escherichia coli STb Enterotoxin Dislodges Claudin-1 from Epithelial Tight Junctions - Nassour, Hassan (PLoS One, 2014)
Enterotoxigenic Escherichia coli produce various heat-labile and heat-stable enterotoxins. STb is a low molecular weight heat-resistant toxin responsible for diarrhea in farm animals, mainly young pigs. A previous study demonstrated that cells having internalized STb toxin induce epithelial barrier dysfunction through changes in tight junction (TJ) proteins. These modifications contribute probably to the diarrhea observed. To gain insight into the mechanism of increased intestinal permeability following STb exposure we treated human colon cells (T84) with purified STb toxin after which cells were harvested and proteins extracted. Using a 1% Nonidet P-40-containing solution we investigated the distribution of claudin-1, a major structural and functional TJ protein responsible for the epithelium impermeability, between membrane (NP40-insoluble) and the cytoplasmic (NP-40 soluble) location. Using immunoblot and confocal microscopy, we observed that treatment of T84 cell monolayers with STb induced redistribution of claudin-1. After 24 h, cells grown in Ca(++)-free medium treated with STb showed about 40% more claudin-1 in the cytoplasm compare to the control. Switching from Ca(++)-free to Ca(++)-enriched medium (1.8 mM) increased the dislodgement rate of claudin-1 as comparable quantitative delocalization was observed after only 6 h. Medium supplemented with the same concentration of Mg(++) or Zn(++) did not affect the dislodgement rate compared to the Ca(++)-free medium. Using anti-phosphoserine and anti-phosphothreonine antibodies, we observed that the loss of membrane claudin-1 was accompanied by dephosphorylation of this TJ protein. Overall, our findings showed an important redistribution of claudin-1 in cells treated with STb toxin. The loss of phosphorylated TJ membrane claudin-1 is likely to be involved in the increased permeability observed. The mechanisms by which these changes are brought about remain to be elucidated.